A Comparison of China and Malaysia in International Business Negotiation - Pin Lick, Soo Hoo (Jurnal The Messenger, 2019)
The real negotiation world particularly cross-cultural negotiation is very challenging and competitive compared to domestic negotiation as each party needs to have cultural intelligence when it comes to international business environment. As many companies are going global, seeking international growth as an importer-exporter, international business negotiation skills are very much needed. The participants in this study were Chinese and Malaysian business negotiators involved in China-Malaysia business. One hundred questionaires were conducted by sending emails or through WeChat to the participants who are based in China. In fact, China s One Belt One Road s plan has created plenty of opportunities for Malaysia to collaborate with Chinese government officials and business leaders in different areas. Based on our analysis, we found that between the two groups of Chinese and Malaysian business negotiators, interdependent self-contrual mediated the relation between cultural norms and interaction goals.